The Application of the Question-and-Answer Method to Enhance the Critical Thinking Skills of High School Students - Rahayu Nugraheni; Lailatul Ramadani; Auliaul Habibah Rosyidi; Nur Wiji Sholikin (Yayasan Insan Mulia Bima, 2026)
The low critical thinking skills of 10th-grade high school students regarding arithmetic sequences and series are attributed to a lack of student engagement during the mathematics learning process. This study aims to determine the effect of implementing the question-and-answer method on improving students' critical thinking skills in the topic of arithmetic sequences and series. A quantitative approach was employed using a quasi-experimental design—specifically, a pretest-posttest control group design. The research subjects consisted of 26 10th-grade students from MA Wahid Hasyim during the 2025/2026 academic year. Data collection involved pretests, posttests, and observation sheets. Data analysis was conducted using normality and t-tests with the aid of IBM SPSS Statistics. The results indicate that the question-and-answer method successfully improved students' critical thinking skills, evidenced by the rise in the average score from 75 on the pretest to 88 on the posttest. Furthermore, the t-test yielded a significance value of 0.001 (p < 0.05), demonstrating that the question-and-answer method had a significant impact on enhancing students' critical thinking skills regarding arithmetic sequences and series.